Inhibiting scar formation via wearable multilayer stacked electret patch: Self‐creation of persistent and customizable DC electric field for fibrogenic activity restriction - Sung‐Won Kim; Sumin Cho; Donghan Lee; Jiyu Hyun; Sunmin Jang; Inwoo Seo; Hyun Su Park; Hee Jae Hwang; Hyung‐Seop Han; Dae Hyeok Yang; Heung Jae Chun; Suk Ho Bhang; et al. (InfoMat, 2024)
Abstract Electrical stimulation has recently received attention as noninvasive treatment in skin wound healing with its outstanding biological property for clinical setting. However, the complexity of equipment for applying appropriate electrical stimulation remains an ongoing challenge. Here, we proposed a strategy for skin scar inhibition by providing electrical stimulation via a multilayer stacked electret (MS‐electret), which can generate direct current (DC) electric field (EF) without any power supply equipment. In addition, the MS‐electret can easily control the intensity of EFs by simply stacking electret layers and maintain stable EF with the surface potential of 3400 V over 5 days owing to the injected charges on the electret surface. We confirmed inhibition of type 1 collagen and α‐SMA expression of human dermal fibroblasts (hDFs) by 90% and 44% in vitro, indicating that the transition of hDFs to myofibroblasts was restricted by applying stable electrical stimulation. We further revealed a 20% significant decrease in the ratio of myofibroblasts caused by the MS‐electret in vivo. These findings present that the MS‐electret is an outstanding candidate for effective skin scar inhibition with a battery‐free, physiological electrical microenvironment, and noninvasive treatment that allows it to prevent external infection.